Usage of Iraqi Surfactant Modified Zeolite for Treatment of Water Produced from Oil Production Processes. - Taher, Muna B.; Abdul Latif , Mohammed H.; Al- Saidy, A. Amer W.; Al- Baldawi, Mayadah N.; Abudi , Weffa T.; Aouda , Athman M.; Zgali, Zainab A. (Journal of Petroleum Research and Studies, 2014)
This study aimed to remove the oil from the produced water imported from Pai- Hassan field using akashat Iraqi natural zeolite after organic modification with cationic surfactant Hexadecyl Trimethyl Ammonium Bromide (HDTMA) solutions as a numerical complication of critical micelles concentration (CMC) of HDTMA (1CMC, 3CMC, .to 13CMC) solutions. Measuring the Electrical Conductivity (EC) of supernatant, and FT-IR, XRD characterization of solid modified Na/HDTMA zeolite indicates that the optimum HDTMA concentration for zeolite modification is (11 CMC) at 65 C°, and the optimum zeolite weight at constant volume (30 ml) of surfactant solution is 2 g. zeolite. Also the removal % of oil from produced water at optimum conditions is 91%.